Reimagining the broader impacts criterion in the NSF graduate research fellowship - Estien, Cesar O.; Quintana, Brandon; Olivares-Zambrano, Daniel (Frontiers in Education, 2022)
For graduate students, securing prestigious fellowships provides incredible benefits such as increased job opportunities and likelihood of receiving awards. These benefits can be particularly life-changing for a graduate student who may come from a marginalized background. However, the inequity in fellowship distribution hinders the success of graduate students, especially those who are marginalized. The majority of the National Science Foundation’s Graduate Research Fellowship Program (GRFP) is white and attend top-ranked institutions. Within the GRFP, there is a clear disconnect between the grantee’s proposed broader impacts and follow-through. To value and support communities, and graduate students of color in the process, the GRFP must be reimagined. In this article, we provide a brief background on the relationship between STEM and marginalized communities, and how broader impacts currently function as a band-aid to the issues of justice, equity, diversity, and inclusion in STEM. We then conclude by providing recommendations to improve the broader impacts section and the awardee selection process.